Two shining souls : Jane Addams, Leo Tolstoy, and the quest for global peace - Cracraft, James (Lexington Books, 2012)
In his new book, Two Shining Souls, James Cracraft explores the decades-long encounter of Jane Addams, the famous American social reformer and peace activist, with Leo Tolstoy, the acclaimed Russian writer and sage. He documents Tolstoy’s influence in Progressive-era America and particularly on Addams’s career, citing previously unknown or neglected sources. In addition to her study of Tolstoy’s writings—his now largely forgotten religious tracts more than his celebrated fiction—Addams traveled to Russia to see him personally, a meeting that is recounted in detail. Late in her life, Addams described Tolstoy as a rare “shining soul,” a term, Cracraft suggests, that applies equally well to her. His book adds an enduring religious dimension to Addams’s rich legacy while newly delimiting, by contrast, the legacy of Tolstoy.